Repercussões da estimulação sensório-motora oral no crescimento e estado nutricional de crianças nascidas pré-termo - Ferreira, Pamela Fantinel (2012)
Objective: to verify the growth, nutritional status, the prevalence and duration of breastfeeding and the introduction of complementary foods in preterm infants which participated in a program of sensory-oral motor stimulation during the neonatal period. Methodology: 36 infants between 9 and 23 months of corrected age were enrolled. Of total, 21 received sensory-oral motor stimulation and 15 were controls. The assessment of growth and nutritional status included: anthropometric measurements (weight, length, head circumference and triceps skinfold thickness), body composition analysis (Bioelectrical Impedance (BIA)) and biochemical evaluation. We also investigated the breastfeeding duration, the age and difficulties to introduce complementary foods and some family and maternal variables. Results: Most of infants had weight and length appropriate for age and sex, however there was a significant reduction in the percentage of stimulated infants with length and head circumference below the 10th percentile in relation to birth, compared with controls. The results from BIA were similar in both groups, with phase angle values equivalent to those found in term and healthy infants. Serum iron was lower in stimulated infants compared with controls (p<0,05). No significant differences were found for the others biochemical values. The prevalence of iron deficiency anemia was 14.3% in stimulated infants and in 6.7% of controls (p>0.05). 52.4% of the stimulated infants were breastfeeding compared with 40% of controls. The duration of breastfeeding was 88.6 ± 72.3 days and 101.67 ± 67.3 days for stimulated and controls infants, respectively. The complementary foods were introduced before six month of age, in both groups, with a higher percentage of difficulties in controls. Conclusion: Sensory-oral motor stimulation had no influence in the infant s nutritional status, but it showed a positive influence in length and head circumference since there was a significant reduction in the percentage of stimulated infants under 10th percentile for this variables.